Evaluation of three Polymerase chain reaction tests targeting morphological transforming region II, UL-83 gene and glycoprotein O gene for the detection of Human Cytomegalovirus genome in clinical specimens of immunocompromised patients in Chennai, India - Therese KL (Virology Journal, 2006)
Abstract Background Human Cytomegalovirus (HCMV) continues to be an important cause of morbidity and occasional mortality in immunocompromised patients. Polymerase chain reaction (PCR) is the most sensitive and commonly used method for the assessment of HCMV infection in the immunocompromised patients at risk from severe associated clinical manifestations. However, there is little consistency in the qualitative PCR used for different regions of HCMV genome. Therefore, the performance of three Qualitative PCR tests to detect HCMV genome in clinical specimens from immunocompromised patients was evaluated. With pp65 antigenemia assay as the "gold standard", nested PCR for morphological transforming region II (mtr II) and glycoprotein O (gO) gene and uniplex PCR for UL 83 gene were applied on 92 consecutive clinical specimens obtained from 74 immunocompromised patients with clinically suspected HCMV disease. Virus isolation was attempted on 12 clinical specimens from six pp65 antigenemia positive patients. Based on the pp 65 antigenemia results as "gold standard", the sensitivity, specificity, positive predictive value and negative predictive value for each PCR was calculated. Results The PCR targeting mtr II region showed a higher sensitivity (100%) and negative predictive value (100%) than the other two PCRs in detecting HCMV DNA from clinical specimens obtained from different immunocompromised patient population of Chennai region, India. Conclusion The results suggests that the optimal method of detection of HCMV DNA could be achieved by PCR using primer sequences targeting mtr II region of genome of HCMV in Chennai region, India.